Influence Of Employee's Spiritual Motivation On Employee Performance (Empirical Study In Santri Works Of Taarid Tauhid Bandung Foundation) - Iman Aryadi; Laili Rahmawati (Review of Islamic Economics and Finance (RIEF), 2019)
The development of foundations and businesses led by Abdullah Gymnastiar. The question arises as to why this business that is labeled with the heart of management is such a way of developing (not only becoming one of the business centers; it also becomes a "moral workshop"), whether it is due to its leadership, work system, conducive environment, or motivation of its employees. This study aims to determine the effect of spiritual motivation on the performance of employees of the Daarut Tauhiid Foundation in Bandung. The hypothesis proposed in this study is the creed motivation, worship motivation, and muamalah motivation partially and together significantly affect performance. The subjects (samples) in this study were 33 people. The sampling method is purposive sampling. Data obtained through primary data by distributing questionnaires also added to interviews and observations. Secondary data were obtained through records and profiles of Daarut Tauhiid foundation and information from various other sources. Data analysis was performed by multiple regression analysis. As a result, partially or together, it turns out that spiritual motivation does not affect performance. This can be seen from the t-count value of each variable (creed = 0.857, worship = 0.288 and muamalah = 0.971) compared to t-table (2.0395) or t-count 2 and the F-count of 1.935 is smaller than 4. Or the significance level is greater than 0.05, which is 0.14. The lack of spiritual motivation on performance is reasonable because spiritual motivation has become the culture and character of the DT foundation's students. Another thing that should be suspected and needs serious attention is the work environment and leadership of the Foundation, which needs to be changed to be more conducive and decentralized. Students of DT have fulfilled the highest spiritual need in Maslow's hierarchy. But the need for a sense of security (work contract), physiological (primary needs), social needs (AA Gym leadership) is less fulfilled. This is very humane and human because while what distinguishes it from organizations or conventional companies is the intention and approach.